Pengetahuan ibu nifas tentang tradisi mararang dan dampaknya terhadap kesehatan ibu dan bayi di kabupaten Toba Samosir (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: To explore the knowledge of postpartum mother about mararang tradition and its impact on mother and baby health in Toba Samosir Regency.Method: This research uses qualitative design, with focus ethnography approach. Determination of the sample size in this study using purposive sampling. Selection of informants was conducted based on the inclusion criteria according to the research topic. Informant in this research is data collecting done through in-depth interview and observation on 11 informant consisted of 4 maternal mothers, 3 husbands / family of postpartum mother, 3 midwife and 1 head of health service of mother and child in health office of Toba Samosir Regency , and Focus Group Disscussion on 6 midwives of Puskesmas.Results: Mararang tradition is believed to be a post-partum treatment that benefits health, where postpartum feels quick to recover from postpartum pain, strong backbone, warm body and sweating and facilitate puerperal expulsion. Informants know smoke from mararang is dangerous for mother and baby respiration. According to the parents of this mararang tradition should be done by postpartum so that make puerper mothers more confident to do mararang tradition. Specific education to stop the tradition of mararang never done, even there are still health workers who participate in mararang tradition.Conclusion: Mararang tradition is still difficult to be abandoned because it is still believed to be beneficial to health and not yet well understood that the impact of mararang tradition can disrupt the health of mother and baby. Families, especially mothers and husbands still strongly support the tradition of mararang. Health workers have not made efforts to provide information and knowledge about the risks and impacts of mararang tradition on maternal and infant health.